Antenatal maternal medication administration in preventing respiratory distress syndrome of premature infants: A network meta‐analysis. (27th September 2018) - Zhang, Haoyang; Liu, Jing; Liu, Tianhao; Wang, Yu; Dai, Weidan
Abstract: Introduction: High incidence of respiratory distress syndrome (RDS) was revealed in preterm infants, which acted as one of the main factors that led to infant death. Objectives: This network meta‐analysis (NMA) was performed to rank the efficacy of different therapies in preventing for premature infants. Methods: PubMed, Embase, Cochrane Library, CINAHL, and CNKI were searched. Statistical analysis was performed using STATA statistical software (Version 12.0). Odds ratios (ORs) with 95% credible intervals (95%CrIs) were applied to evaluate relative efficacy of various treatments. Ranking of probabilities of each treatment was illustrated by surface under the cumulative ranking curve (SUCRA). Consistency between direct and indirect evidence was assessed using the node‐splitting plots and heat plots. Results and conclusion: A total of 48 trials were eligible to evaluate the efficacy of 3 interventions including ambroxol (AMB), betamethasone (BET), and dexamethasone (DEX). Three outcomes including the incidence of RDS, bronchopulmonary dysplasia (BPD) and neonatal death were assessed. Compared with placebo, BET, DEX, and AMB all demonstrated better efficacy in terms of preventing RDS and neonatal death. No significant difference among treatments was found in the assessment of the incidence of BPD. According to SUCRA, AMB was the optimal treatment in preventing RDS and neonatal death. Besides, no significant inconsistency was detected between direct and indirect evidence. To conclude, no significant difference was found among these three medications. AMB seems to have the potential to be the most effective treatment for reducing the incidence of RDS and neonatal death.